2021
DOI: 10.1029/2020jg006065
|View full text |Cite
|
Sign up to set email alerts
|

Winter Oxygen Regimes in Clear and Turbid Shallow Lakes

Abstract: Dissolved oxygen levels in lake water control multiple physical and biological processes. Anoxia is defined as the absence of oxygen, though waters are often considered anoxic when oxygen concentrations fall below 1 g m −3 (Nürnberg, 1995). Anoxia can directly impact aquatic organisms as well as exert control over important chemical reactions. Low oxygen concentrations can lead to fish kills (Greenbank, 1945), with effects on fish community composition (Tonn & Magnuson, 1982) and the food web structure of lake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 117 publications
1
13
4
Order By: Relevance
“…Contrary to expectation, we did not observe a shift in NEP across seasons. Unlike previous studies in which NEP shifted from positive to negative between summer and winter (Rabaey et al, 2021), leading to changes in annual…”
Section: Inter and Intra-annual Variability In Lake Metabolismcontrasting
confidence: 87%
See 1 more Smart Citation
“…Contrary to expectation, we did not observe a shift in NEP across seasons. Unlike previous studies in which NEP shifted from positive to negative between summer and winter (Rabaey et al, 2021), leading to changes in annual…”
Section: Inter and Intra-annual Variability In Lake Metabolismcontrasting
confidence: 87%
“…Journal of Geophysical Research: Biogeosciences 10.1029/2024JG008057 metabolism estimates (Brentrup et al, 2021), FCR exhibited similar NEP year-round (Figure 4c). This consistency across seasons may be potentially due to FCR's short ice cover duration or because it is a human-made reservoir and therefore may exhibit fundamentally different patterns of ecosystem functioning than the naturally-formed lakes examined by Brentrup et al (2021) and Rabaey et al (2021).…”
Section: Inter and Intra-annual Variability In Lake Metabolismmentioning
confidence: 98%
“…Rabaey et al. (2021) observed similar DO dynamics in these systems in the open water seasons (spring, summer, and fall), while in winter under ice, there were greater oxygen depletion rates in the clear lakes, likely a consequence of degradation of the accumulated plant biomass without ingress from the atmosphere. Coupled with observations that clear lakes have lower N:P ratios than turbid lakes, likely due to increased denitrification (Ginger et al., 2017), it may be that winter provides some “memory” that is manifest throughout the year in these shallow lakes.…”
Section: Physical and Biogeochemical Dynamicsmentioning
confidence: 80%
“…Microbial respiration under ice consumes autochthonous organic matter accumulated from the previous summer (Meding & Jackson, 2003;Powers et al, 2017). Previous studies have also shown that under-ice dissolved oxygen at the sediment-water interface is inversely related to the Journal of Geophysical Research: Biogeosciences 10.1029/2024JG008120 previous summer's maximum chl a concentration (Finlay et al, 2019;Terry et al, 2017) and macrophyte biomass (Meding & Jackson, 2003;Rabaey et al, 2021) in eutrophic, temperate, shallow lakes. The phytoplankton abundance and diversity can be similar between urban ponds and shallow lakes (Minelgaite et al, 2020) and floating macrophyte coverage can dominate small pond ecosystems (Gee et al, 1997).…”
Section: Drivers Of Under-ice Oxygenmentioning
confidence: 99%